PENGARUH LUAS LAHAN DAN JUMLAH PRODUKSI TERHADAP EKSPOR KARET ALAM DI INDONESIA - Muhammad Nazfa Ibnu; Khairil Anwar; Cut Putri Melita Sari; Umaruddin Usman (LPPM Universitas Malikussaleh - Indonesia, 2022)
This study examined the effect of price, exchange rate, and production on Indonesian seaweed exports to Europe. The reason is that in 2016 the price of seaweed was lower than the previous year, but there was a decline in exports. The data analysis method used was panel data analysis because the data used was a combination of cross-section and time series data. The results partially indicated that the price and exchange rate positively and significantly affected Indonesian seaweed exports, while the exchange rate negatively and insignificantly affect Indonesian seaweed exports. Simultaneously, the exchange rate and seaweed production positively and significantly affected Indonesian seaweed exports.